Doping Strategies for Enhancing ZnO-Based Photodetectors: A Comprehensive Review - Prayogo, Priyan; Eliyana, Ajeng; Satria, Eko; Pardede, Indra (Universitas Islam Negeri Raden Intan Lampung, Indonesia, 2025)
The performance of ZnO-based nanostructured photodetectors has garnered significant interest due to their potential for high sensitivity and fast response in ultraviolet and optoelectronic applications. This review aims to comprehensively analyze recent advancements in enhancing ZnO photodetector performance through single doping and codoping strategies. This study synthesizes findings from peer-reviewed research articles published over the past five years. The results indicate that specific dopants, such as F, Mg, Ti, and Co+Ni, significantly improve key performance parameters, including responsivity, sensitivity, and detectivity. Codoping approaches, particularly with In+Ga or Sn+Ti, exhibit synergistic effects that further enhance carrier mobility and reduce trap states, resulting in external quantum efficiencies exceeding 10⁹%. The review concludes that the careful selection and concentration of dopants, nanostructure design, and scalable fabrication methods are crucial for optimizing ZnO-based photodetectors. This work contributes by offering a structured synthesis of performance trends, identifying research gaps, and outlining future directions for developing high-performance and industry-ready ZnO photodetector technologies.